Comparative characteristic of anterior and posterior stabilization of the cervical spine during surgical interventions - Aleksandr V. Burtsev; Alexandr V. Gubin; Sergey O. Ryabykh; Olga M. Sergeenko (Pavlova); Polina V. Ochirova (Хирургия позвоночника, 2020)
Objective. To analyze possibilities and limitations of various stabilization technologies in the surgical treatment of cervical spine pathology. Material and Methods. Study design: retrospective monocentric observational analysis. Level of evidence: 3b (UK Oxford, version 2009). Diagnostic and treatment data are presented for 433 patients operated on using stabilization systems: patients in Group 1 (n = 228) underwent anterior fixation, those in Group 2 (n = 175) – posterior fixation with polyaxial screw systems, and in Group 3 (n = 30) – combined (anterior and posterior) fixation. Results. For anterior fixation, ACDF, ACCF and their combinations were used as stabilization technologies. In 18.0 % of patients, 49 complications were revealed which corresponded to the 1st and 2nd categories according to the recommendations of WHO, and to grades I– IVA of Clavien – Dindo classification. For posterior fixation in Group 2, stabilization was performed using screw instrumentation systems. In 13.7 % of patients, 25 complications of the 1st and 2nd categories according to WHO recommendations and grades I–V according to Clavien-Dindo classification were revealed. Combined fixation involved the use of both anterior and posterior stabilizations. Analysis of anterior and posterior fixation techniques, as well as their comparison, showed a wide range of posterior stabilization options for a surgeon: any age, length, localization and nosology. Moreover, the realization of these advantages is carried out only through the indispensable use of screw fixation. Posterior fixation has several limitations: the impossibility of anterior decompression, limited correction of segmental lordosis, accessibility and greater trauma to soft tissues. Conclusion. Comparative analysis of methods for the cervical spine stabilization showed that posterior fixation is an integral part of the surgical treatment of the cervical spine pathology. The obtained results indicate the complementarity of the technologies for the cervical spine stabilization, without their interchangeability. These data can be useful when choosing stabilization techniques before planning surgical treatment of cervical spine pathology, which will allow changing the existing paradigm.